Diffraction of Resonance X-Ray Transition Radiation of 900 MeV Electrons Under Condition of Generation of 20 KeV Parametric X-Ray Radiation in (110) Ge Crystal - Andreyashkin M. Yu.; Kaplin V. V. Valeriy Viktorovich; Potylitsyn A. P. Alexander Petrovich; Zabaev V. N. Viktor Nikolaevich; Uglov S. R. Sergey Romanovich (1993, 1993)
В фонде НТБ ТПУ отсутствует